Deafferentation of the Superior Colliculus Abolishes Spatial Summation of Redundant Visual Signals - van Koningsbruggen, Martijn; Koller, Kristin; Rafal, Robert D. (Frontiers in Systems Neuroscience, 2017)
Two visual signals appearing simultaneously are detected more rapidly than either signal appearing alone. Part of this redundant target effect (RTE) can be attributed to neural summation that has been proposed to occur in the superior colliculus (SC). We report direct evidence in two neurological patients for neural summation in the SC, and that it is mediated by afferent visual information transmitted through its brachium. The RTE was abolished in one patient with a haemorrhage involving the right posterior thalamus that damaged part of the SC and that disrupted its brachium; and in another patient in whom the SC appeared intact but deafferented due to traumatic avulsion of its brachium. In addition reaction time for unilateral targets in the contralesional field was slowed in both patients, providing the first evidence that visual afferents to the superior colliculus contribute to the efficiency of target detection.